Я познаю мир : География: энциклопедия / автор-составитель В. А. Маркин (АСТ, 1997)
Экземпляры: ф.1 (20220923) / Инвентарный номер: 60689 / Цена: 109.00 / Сис.шифр: 26.8 / Авт.знак: Я 11 / ББК: 26.8я2